Static and dynamic interactive buckling regarding axial extension mode of thin-walled channel - Kołakowski, Zbigniew (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2010)
The present paper deals with an influence of the axial extension mode on static and dynamic interactive buckling of a thin-walled channel with imperfections subjected to uniform compression when the shear lag phenomenon and distortional deformations are taken into account. A plate model is adopted for the channel. The structure is assumed to be simply supported at the ends. Equations of motion of component plates were obtained from Hamilton's principle taking into account all components of inertia forces. In the frame of first order nonlinear approximation, the dynamic problem of modal interactive buckling is solved by the transition matrix using the perturbation method and Godunov's orthogonalization.

W prezentowanej pracy omówiono wpływ osiowej wzdłużnej postaci na statyczne i dynamiczne interakcyjne wyboczenie cienkościennego ceownika z niedokładnościami poddanego równomiernemu ściskaniu przy uwzględnieniu zjawiska shear-lag oraz dystorsyjnej deformacji. Przyjęto płytowy model ceownika. Konstrukcja jest przegubowo podparta na obu końcach. Równania ruchu płyt składowych otrzymano z zasady Hamiltona, biorąc pod uwagę wszystkie składowe sił bezwładności. Dynamiczne zagadnienie modalnego interakcyjnego wyboczenia w ramach pierwszego rzędu nieliniowej aproksymacji rozwiązano metodą macierzy przeniesienia i metodą ortogonalizacji Godunova.
Statyczne i dynamiczne interakcyjne wyboczenie cienkościennego ceownika uwzględniające osiową postać wzdłużną.
Keywords: thin-walled structures; dynamic interactive buckling; axial mode; konstrukcje cienkościenne; dynamiczne interaktywne wyboczenie; tryb osiowy; płytowy model ceownika; zasada Hamiltona; metoda macierzy przeniesienia